Reinvigorating the Non-Aligned Movement for the post-COVID-19 era - Yuefen Li; Daniel Uribe Terán; Danish (South Centre, 2023)
The Non-Aligned Movement (NAM) was born out of the need felt by newly emerging post-colonial nations not to be compelled to be part of any single political or military bloc during the Cold War. As the international community finds itself once again in the midst of heightened geo-political tensions, the principles of non-alignment have seen a resurgence in the Global South, providing NAM with the potential to become a major force in the configuration of a new international order. Over six decades after its inception, the NAM stands at a crucial juncture, where consolidating non-alignment among developing countries can help build solidarity, promote collaboration and defend the interest of developing countries in the reconfiguration of global governance. Dealing with these challenges requires unprecedented levels of international cooperation, both North-South and South-South. As the grouping of non-aligned countries, the NAM could play an important role against global fragmentation, build solidarity, and strengthen multilateralism. This paper therefore looks at the role and position of the NAM at this time, and how it can be reinvigorated to address the most critical challenges facing its Member States and other developing countries today. Considering the history, evolution and important achievements of the NAM, the paper provides some proposals that can support NAM Member States in their recovery from the COVID-19 pandemic and make progress in implementing the 2030 Agenda for Sustainable Development.
Keywords: 300; 2030 Agenda for Sustainable Development; Climate Change; Decolonisation; Decolonization; Digital Transformation; Environmental Protection; Global South; International Cooperation; Multilateralism; New International Economic Order; Non-Aligned Movement (NAM); North-South Cooperation; Peace and Security; Post COVID-19; Right to Development (RtD); Solidarity; South-South and Triangular Cooperation (SSTrC); South-South Cooperation; Sustainable Development Goals (SDGs); Triangular Cooperation; United Nations (UN)